Use of preheated resin as a cementitious material in indirect restoration: A literature review (Research, Society and Development, 2021)
Due to the great aesthetic appeal over the years associated with minimally invasive techniques, contemporary dentistry bets on materials with excellent aesthetic and mechanical characteristics, so dentists seek to bet on the use of pre-heating of composite resins as a cementitious material for restorations indirect, since its optical and mechanical properties propose a better aesthetic and a better marginal adaptation compared to resin cements. The objective of this work is to review the literature about the optical and mechanical characteristics of the different materials used as cementing agents in indirect restorations, emphasizing long-term color stability, marginal adaptation, toxicity, degree of conversion of monomers and clinical practicality. For this purpose, an electronic search was performed in the Online Medical Literature Search and Analysis database (PubMed), using the following descriptors in English: thermoactivated resin, temperature and dental veneers, registered in the Mesh (Medical Subject Headings) combined between itself by the Boolean operator “AND”. After delimiting the search for 10 years, 50 articles were found. Of these, 13 studies were selected, based on the reading of titles and abstracts. In short, preheated resins have excellent mechanical and optical characteristics, however it is up to the dentist to choose which technique is most feasible in his clinical practice.